Recombinant Tumor Suppressor TSC1 Differentially Interacts with Escherichia coli DnaK and Human HSP70 - Natarajan, Nalini; Shaik, Althaf; Thiruvenkatam, Vijay (ACS omega, 2020)
Tuberous sclerosis complex (TSC) is a neurological syndrome manifested by non-cancerous tumors in several organs. Mutations in either TSC1 or TSC2 tumor suppressor gene cause the disease. In the cell, TSC1 is known to form a heterodimer with TSC2 because of which an active complex is formed that negatively regulates the mTORC1 activity during cellular stress. Hence, mutation in TSC1 or TSC2 is manifested by excess proliferation of the cells leading to the development of numerous benign tumors. The TSC1 and TSC2 complex is known to interact with several protein-binding partners. One such significant interaction of this complex is with the molecular chaperone HSP70. The role of TSC1 in that interaction is still elusive. Here, we have expressed and purified TSC1 (302–420 residues) in a bacterial expression system and have shown that this region directly interacts with HSP70. We have shown that TSC1 increases the ATPase activity of Escherichia coli DnaK, a HSP70 homologue. On the contrary, TSC1 was found to show inhibitory activity toward human HSP70. Our result suggests that TSC1 (302–420 aa) shows differential interaction between the HSP70 homologues. This points toward the evolutionary significance of chaperoning system and the importance of eukaryotic tetratricopeptide repeat domain interaction motif -EEVD. Our study shows the evidence that TSC1 interacts with HSP70 and has a role to play in the chaperoning activity to maintain cellular homeostasis.